Elevated air humidity affects hydraulic traits and tree size but not biomass allocation in young silver birches (Betula pendula) - Sellin, Arne; Rosenvald, Katrin; Õunapuu-Pikas, Eele; Tullus, Arvo; Ostonen, Ivika; Lõhmus, Krista (Frontiers in Plant Science, 2015)
As changes in air temperature, precipitation, and air humidity are expected in the coming decades, studies on the impact of these environmental shifts on plant growth and functioning are of major importance. Greatly understudied aspects of climate change include consequences of increasing air humidity on forest ecosystems, predicted for high latitudes. The main objective of this study was to find a link between hydraulic acclimation and shifts in trees’ resource allocation in silver birch (Betula pendula Roth) in response to elevated air relative humidity (RH). A second question was whether the changes in hydraulic architecture depend on tree size. Two years of application of increased RH decreased the biomass accumulation in birch saplings, but the biomass partitioning among aboveground parts (leaves, branches, and stems) remained unaffected. Increased stem Huber values (xylem cross-sectional area to leaf area ratio) observed in trees under elevated RH did not entail changes in the ratio of non-photosynthetic to photosynthetic tissues. The reduction of stem-wood density is attributable to diminished mechanical load imposed on the stem, since humidified trees had relatively shorter crowns. Growing under higher RH caused hydraulic conductance of the root system (KR) to increase, while KR (expressed per unit leaf area) decreased and leaf hydraulic conductance increased with tree size. Saplings of silver birch acclimate to increasing air humidity by adjusting plant morphology (live crown length, slenderness, specific leaf area, and fine-root traits) and wood density rather than biomass distribution among aboveground organs. The treatment had a significant effect on several hydraulic properties of the trees, while the shifts were largely associated with changes in tree size but not in biomass allocation.